Propuesta metodológica para estimación de Caudal ecológico en fuentes superficiales. - Oyola Sánchez, Teresa Yolanda (2017)
At present, there is no defined methodology for the estimation of the ecological flow of surface sources, which observes the characteristics of each hydrographic basin environment , considers the dry period (dry season) in the year (June-December) and The availability of the water resource to satisfy the basic needs of water users, thus ensuring that in the downstream flows of the points of the authorization that are granted by the Single Water Authority, an ecological flow flows permanently that avoid the risk of damage to the aquatic ecosystem of rivers. The present investigation is to develop a methodological proposal by request of hydrometric information for the estimation of the ecological flow of superficial sources To achieve this, a review, compilation, and systematization of bibliographical information were carried out relating to the methodologies: hydrological, hydraulic, and simulation of habitat and its holistic environment. We can then provide a brief summary and perform comparative analyses of its advantages, disadvantages, complexity, and injunction of information. Then the criteria and procedures were determined to be used in accordance with the environment of the localized surface sources in the middle and lower basin of the Jubones River. As a result, a methodological proposal that, applying the Tennant method with the modification of the ecological post-evaluation of the study section, establishes an ecological flow for the whole year equivalent to 10% of the average annual flow as the minimum to conserve the ecosystems of The surface sources.